PENGARUH PEMAHAMAN AKUNTANSI, MOTIVASI BERKEMBANG DAN KEBUTUHAN PENDANAAN TERHADAP PENGGUNAAN INFORMASI AKUNTANSI (Studi Kasus Pelaku UMKM di Kabupaten Sleman) - Retsa Herlin Perliana (Bajang Institute, 2022)
Accounting information is quantitative information containing economic units that are used in the process of determining economic decisions for an action and to assess company performance. The purpose of this study was to determine the effect of accounting understanding, development motivation and funding needs on the use of accounting information. This study uses a quantitative descriptive method with a research sample of 100 respondents who are MSME actors in the Sleman Regency area. Based on the result of teh study, there is a positive influence between accounting understanding, development motivation and funding needs on the use of accounting information.